2014
DOI: 10.1039/c4em00093e
|View full text |Cite
|
Sign up to set email alerts
|

The use of existing environmental networks for the post-market monitoring of GM crop cultivation in the EU

Abstract: The European Union (EU) Directive 2001/18/EC on the deliberate release of genetically modified organisms (GMOs) into the environment requires that both Case-Specific Monitoring (CSM) and General Surveillance (GS) are considered as post-market implementing measures. Whereas CSM is directed to monitor potential adverse effects of GMOs or their use identified in the environmental risk assessment, GS aims to detect un-intended adverse effects of GMOs or their use on human and animal health or the environment. Guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
0
20
1
Order By: Relevance
“…Overall summary reports with graphs, communications, distribution maps and other publications are made publicly available (Smets et al, 2014). While they represent a contextual interpretation, they may not allow subsequent analysis and/or interpretation with other datasets owing to, for example, different methodology or different parameters.…”
Section: Concerns Pertaining To Data Ownership and Availabilitymentioning
confidence: 99%
“…Overall summary reports with graphs, communications, distribution maps and other publications are made publicly available (Smets et al, 2014). While they represent a contextual interpretation, they may not allow subsequent analysis and/or interpretation with other datasets owing to, for example, different methodology or different parameters.…”
Section: Concerns Pertaining To Data Ownership and Availabilitymentioning
confidence: 99%
“…However, the GMO Panel notes that efforts have been made to develop a methodological framework to facilitate the use of existing networks in the broader context of environmental monitoring (Centre for Ecology and Hydrology, Perseus et al, 2014;EFSA GMO Panel, 2014b;Smets et al, 2014). The GMO Panel encourages that these efforts are continued by relevant parties (EFSA GMO Panel, 2011b The search strategy 29 used for the literature search was similar to that applied in the search reported in the previous annual PMEM report (for further details see EFSA GMO Panel, 2016).…”
Section: Existing Monitoring Networkmentioning
confidence: 99%
“…In this external report and other publications (e.g. Smets et al, 2014), several existing networks were identified as potentially suitable for GS of GM plants, although their usefulness is limited due to issues pertaining to data accessibility, data reporting format, and data connectivity with GMO registers (EFSA GMO Panel, 2014b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations